Audit Operasional dan Meningkatkan Efisiensi serta Efektivitas Produksi (Sebuah stusi pada PT. Budi Acid Jaya) - Iskandar Ali Alam; . Imelda; Riswan RISWAN (Jurnal Akuntansi dan Keuangan, 2011)
The purpose of this study was to determine the role of operational checks in assisting the implementation of production activities within a company. Motivation of this study originated from the operational audit issues that can encourage savings, efficiency and effectiveness of activities and also to assess whether management practices are applied in these activities are already well underway. The research was conducted at PT. Budi Acid Jaya using qualitative analysis methods. The data obtained by conducting interviews with company staff concerned, as well as through literature research. Then these data are compared, the theory of what happened in the company, and provide an account based on the theory clearly related to the subject matter. Based on the analysis, it can be concluded that the operational audit on production at PT. Budi Acid Jaya did not play well so the authors provide suggestions that are expected to be useful to reduce and solve the weaknesses of the company.